Understanding gender inequity in brain health outcomes: missed stroke as a case study for intersectionality - Berkhout, Suze G.; Hashmi, Syeda; Pikula, Aleksandra (Frontiers in Global Women's Health, 2024)
The one thing I keep going back to is the night of the stroke, in the first hospital, the nurses clearly didn't recognize the symptoms. Or, they didn't recognize the symptoms in a younger female. That, to me, is intensely problematic for very obvious reasons. The whole experience was so bad that I was actually encouraged by one of my neurologists in [that city] to launch a complaint.Recent attention into sex and gender-based inequities surrounding outcomes for brain health i disorders has generated momentum toward addressing what has been called the "brain health gap." From translational research to health policy and structural change, disparities in understanding the prevalence, detection, and treatment of many forms of brain-related illness that disproportionately impact women have received increased attention (Giralt et al. 2012). Mechanisms for changing these disparities are increasingly called in (Smith et al. 2021;Thomas et al. 2021;Ovbiagele 2020). Importantly though, "women" are not uniform demographic group. Various scholarly fields-notably within Black Feminist and critical race scholarship, and more recently what has been termed "crip of colour" critiques from within disability studies ii -have highlighted the ways in which the intersections and interactions of racism, patriarchy, ableism and heteronormativity (amongst other dimensions of social power) are crucial for understanding and addressing health-related inequity (Kelly et al. 2022;Schalk and Kim 2020).